Регрессионная модель нагрева стенки резервуара при пожаре в резервуарном парке - Басманов, А. Е. (НТУ "ХПИ", 2005)
Regression model which describing dependence of wall temperature of the tank, versed to a torch of the shining tank. Its adequacy was checked. There are next thermal parameters was analized: coefficients of blackness of the tank and petroleum, thermal capacity and density of gas vapour mixture, coefficient of heat convection.
Keywords: математическая модель; распределение температуры; паровоздушная смесь; нефтепродукт; факел; самовоспламенение; регрессия